Research in social movements, conflicts and change. Vol. 22 - Coy, Patrick G. (JAI, 2000)
The contents of this volume reflect the multiple foci that have historically defined the series. We present here two papers on methodological issues facing the study of social movements, four papers on specific social movements or social movement organizations (including two on environmental movements), two papers on aspects of social change and inequality, and one study critically analyzing the conflict resolution prospects in a situation of protracted violence.